Pengembangan LKS berbasis konflik kognitif terintegrasi literasi baru pada materi fluida untuk siswa kelas XI SMA - Siti Asma hanum; Fatni Mufit; As rizal (PILLAR OF PHYSICS EDUCATION, 2019)
The era of the industrial revolution 4.0 which views information technology as a basis in human life. Education is demanded to be able to improve quality human resources. The 2013 revised 2017 curriculum is the government's effort to answer the demands of the industrial revolution 4.0 era which aims to shape literacy in students. However, the reality of school shows that student literacy has not been well implemented and understanding of Physics concepts is still low. One solution to overcome these problems is to develop a physics conflict cognitive worksheet based on students. The purpose of this study is to determine the validity and practicality of Physics students' worksheets. Research conducted includes the type of Development Research research using the Plomp model. The object of the study was a cognitive conflict based student worksheet. Data source validation results from experts by the Physics lecturer at the Faculty of Mathematics and Natural Sciences UNP, the results of practicality from the Physics teacher, as well as the results of the practicality of one to one and small groups of class XI students of SMAN 7 Padang. Based on data analysis two research results can be stated. First, cognitive conflict based LKS is very valid. Second, the use of cognitive conflict based student worksheets is very practical. So, it can be concluded that the worksheet based on cognitive conflict integrated with new literacy on fluid material for class XI high school students is valid and practical.